Пояснение:
(1) Одна из формул сокращённого умножения:
(a + b) (a - b) = a² - b²;
(2) Раскрытие скобок в общем виде:
a (b ± c) = ab ± ac.
Решение:
(x + 5) (x - 5) - x (x - 10) =
= x² - 5² - x² + 10x =
= (x² - x²) + 10x - 25 =
= 10x - 25.
Ответ: 10x - 25.
__________
Удачи Вам! :)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пояснение:
(1) Одна из формул сокращённого умножения:
(a + b) (a - b) = a² - b²;
(2) Раскрытие скобок в общем виде:
a (b ± c) = ab ± ac.
Решение:
(x + 5) (x - 5) - x (x - 10) =
= x² - 5² - x² + 10x =
= (x² - x²) + 10x - 25 =
= 10x - 25.
Ответ: 10x - 25.
__________
Удачи Вам! :)